Role of aquatic macrophytes in maintaining ecosystem stability - S, Muthuraj; Parashar, Tarun; Sidhu, Jaspreet; Mishra, Subhrajyoti; R, Murugan; M. Sonavale, Rahul; Kumar Yadav, Puneet (International Journal of Aquatic Research and Environmental Studies, 2026)
Aquatic macrophytes are important in stabilizing freshwater ecosystems by controlling nutrient circulation, increasing biodiversity, and improving water quality. Such plants, such as submerged, emergent, and floating plants, play a role in ecosystem processes such as stabilizing sediments, up taking nutrients, and providing habitats. The aim of this research was to determine the ecological processes of macrophytes and their contribution to ecological stability, especially in reducing eutrophication and enhancing water clarity. This research used field surveys, statistical data, and experimental data to quantify the impacts of macrophytes on nutrient content, sediment stability, and biodiversity in freshwater environments. In statistical analysis, submerged macrophytes decreased nutrient levels by a factor of up to 50, and the coverage of macrophytes resulted in a 25% increase in species richness in restored systems. Macrophytes also greatly improved water clarity, and the resuspension of sediment decreased by 30%. The outcomes show that macrophytes play a vital role in supporting the health of the ecosystem, particularly in stressful environments such as nutrient overload and invasive species. The paper finds that macrophytes are critical ecosystem service providers and resistant to environmental change. The next generation of work on the topic should be devoted to long-term restoration, the use of molecular tools to research the interaction of plants and microorganisms, and the development of adaptive management plans to preserve macrophytes in urbanized and nutrient-enriched watershed systems. These results indicate that interdisciplinary research and ecosystem-based management services are necessary to maintain the ecological value of freshwater systems, which can support sustainable biodiversity and water quality when various environmental challenges are in place.
Keywords: Aquatic macrophytes; Ecosystem stability; Biodiversity; Nutrient cycling; Eutrophication; Habitat complexity; Resilience; Freshwater ecosystems; Sediment stabilization; Water quality; floating macrophytes